The State of the Planktonic and Benthic Components of the Ecosystem of the Golden Horn Bay (Peter the Great Bay, Sea of Japan) in the Area of the Coal Terminal - Smirnova Elena Valerievna (EDP Sciences, 2021)
Monitoring study of the state of the planktonic and benthic components of the ecosystem of the Golden Horn bay, Peter the Great Bay of the Sea of Japan in the area of the coal terminal was carried out in the autumn of 2020. Phytoplankton in the studied area was characterized by a depleted species composition. In September 2020, phytoplankton bloom was noted at the monitoring points, due to the massive development of diatom microalgae of the Chaethoceros genus, which accounted for 90% of the total phytoplankton. In November, the amount of phytoplankton was an order of magnitude lower, and the role of dinophytic algae increased in the community. Changes in the species composition and quantitative parameters of phytoplankton correspond to the seasonal dynamics in the eastern part of the Amursky bay, which is subject of anthropogenic pollution. Based on the study carried out, it can be concluded that the activities of the coal terminal in the Golden Horn bay had no effect on the structure of communities and, in general, there was no over-normative effect on the state of aquatic biological resources.